Processing and recycling of polymer- coated waste paper - Kurta, M.; Voronych, O. (Видавництво Львівської політехніки, 2012)
The technology of recycling polymer coated wall -paper waste was developed. Design included the first stage of shredding waste paper with chopper -disk and milling. During the second stage, shredding was carried out on drum mills with separation of cellulose fiber from polymer coating. The third stage consisted of separation of two fractions: polymer coating and cellulose fiber. As a result of this process, 50 -95% of pure cellulose and 5 -50% solid polymer waste were obtained. Obtained cellulose could be used for technical paper and packaging carton, as structural filler in the construction, etc., polymer -coated wastes are used for construction and composite materials.